A Review of Associations Between Family or Shared Meal Frequency and Dietary and Weight Status Outcomes Across the Lifespan - Fulkerson, Jayne A.; Larson, Nicole; Horning, Melissa; Neumark-Sztainer, Dianne (Journal of nutrition education and behavior, 2014)
To summarize the research literature on associations between family meal frequency and dietary outcomes as well as weight status across the lifespan. Reviewed literature of family or shared meals with dietary and weight outcomes in youth, adults, and older adults. Across the lifespan, eating with others, particularly family, is associated with healthier dietary outcomes. Among children and adolescents, these findings appear to be consistent for both boys and girls, whereas mixed findings are seen by gender for adult men and women. The findings of associations between family or shared meals and weight outcomes across the lifespan are less consistent and more complicated than those of dietary outcomes. Now is the time for the field to improve understanding of the mechanisms involved in the positive associations seen with family meal frequency, and to move forward with implementing interventions aimed at increasing the frequency of, and improving the quality of, food served at family meals, and evaluating their impact. Given the more limited findings of associations between family or shared meals and weight outcomes, capitalizing on the positive benefits of family and shared meals while addressing the types of foods served, portion sizes, and other potential mechanisms may have a significant impact on obesity prevention and reduction. Future research recommendations are provided.